The Influence of Celebrities/Celebrities Endorsers and Shopee E-Commerce on Consumer Purchase Interests of Products: Pengaruh Selebgram/Selebriti Endorser dan E-Commerce Shopee Terhadap Minat Beli Konsumen Produk - Ardiansah, Fani; Rocmaniah, Ainur (Indonesian Journal of Law and Economics Review, 2022)
The study aims to determine the effect of Selebgram/Celebrity Endorser and E-Commerce Shopee on consumer buying interest of Erigo product. The method used in this research is quantitative. The populations in this study were Instagram followers @erigostore with a sample of 205 respondents who were taken using the Slovin Formula’s and using a simple random sampling technique. Data collection is done by ditributing questioners with the help of google form. This study uses multiple linier regression, and data analysis with the help of SPSS 20.0 software. The result of this study indicate that there is an influence of Selebgram/Celebrity Endorser and E-Commerce Shopee on consumer buying interest with an Adjusted R Square value of 0,489 with a contribution of 48,9% independent variables. There result of the T Test show that there is a parsial effect of Selebgram/Celebrity Endorser and E-Commerce Shopee on consumer buying interest in Erigo products. And the result of the F Test shiow the influence of Selebgram/Celebrity Endorser and E-Commerce Shopee on consumer buying interest in Erigo products together or simultan